2 Cardiopulmonary exercise testing excludes clinically significant disease in military patients recovering from COVID-19. Issue 5 (26th September 2022) - Chamley, Rebecca; Holdsworth, David; Barker-Davies, Robert; Bennett, Alexander; O'Sullivan, Oliver; Ladlow, Peter; Houston, Andrew; May, Samantha; Mulae, Joseph; Xie, Cheng; Cranley, Mark; Sellon, Ed; et al.
Abstract : Background: Post-COVID-19 syndrome presents a challenge when determining the occupational grading of symptomatic military personnel, and their ability to deploy. In particular, the accurate assessment of patients with post COVID-19 syndrome is complicated by health anxiety and coincident symptomatic autonomic dysfunction. We therefore sought to determine whether either symptoms or objective cardiopulmonary exercise testing could predict clinically significant findings in the UK Armed Forces. Methods: 113 consecutive patients were assessed in a post COVID-19 military clinical assessment pathway. This included symptom reporting, history, examination, spirometry, echocardiography and cardiopulmonary exercise testing (CPET) in all, with chest CT, dual-energy CTPA and cardiac MRI where indicated. Symptoms, CPET findings and presence/absence of significant pathology were reviewed. Data were analysed to identify diagnostic strategies that may be used to exclude significant disease. Results: 7/113 (6%) patients had clinically significant disease adjudicated by cardiothoracic multi-disciplinary team. These patients had reduced fitness (&Vdot;O2 26.7(±5·1) vs. 34.6(±7·0) ml/kg/min; p = 0·002) and functional capacity (peak power 200 (±36) vs. 247 (±55) Watts; p = 0·026) compared to those without significant disease. Simple CPET criteria (&Vdot;O2 <100% predicted and VE/&Vdot;CO2 slope >30.0 or VE/&Vdot;CO2 slope >35.0 in isolation) excluded significant disease with sensitivity and specificity of 86% and 83% respectively (AUC 0.89). The addition of capillary blood gases to estimate A-a gradient improved diagnostic performance to 100% sensitivity and 78% specificity (AUC 0.92). Symptoms and spirometry did not discriminate significant disease. Conclusion: UK Armed Forces personnel with persistent symptoms post SARS-CoV-2 infection demonstrate reassuringly little organ pathology. CPET and functional capacity testing, but not reported symptoms, allow the exclusion of clinically significant disease.